EFEKTIVITAS PENGGUNAAN BEBERAPA MEREK CAIRAN PENCUCI TERHADAP PENURUNAN JUMLAH ANGKA KUMAN PIRING - Adelia Adelia; Sukesi Wahyuni Tri (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2020)
abstracâ€” Washing the cutlery is one of most simple and common ways to maintain the cleanliness of cutlery in order to fulfill the requirements about the number of germs that is 0 (zero) from the cutlery surface. Dishwashing liquid is a necessary product in the washing process. Dishwashing liquid in the market consists of a various brands, which causes the household to use different dishwashing liquid products. This study aims to determine effectiveness of using several brands diswashing liquids against decreaseÂ  the number of germ on plate.This research type is a quasi experiment with pretest-posttest with control group design. The subjects of this research is the number of germ and the object is plate with treatment of A, B, C, D and E brand dishwashing liquid with three replications. Analisys data use paired sample t-test and kruskall wallis non parametric test.The result of bivariate analysis with paired sample t-test showed there was difference of germs number before and after treatment with A, B and C dishwashing liquid (p <0,05) and there was no difference of germs number before and after treatment with D, E dishwashing liquid and control group (p> 0.05) statistically. The result of kruskal wallis test showed that there was no significant difference against decrease the germs number on plate by using some brands of dishwashing liquid with p value = 0,506.The conclusion of this research is no significant difference against decrease the number of germs on plate by using several brands of dishwashing liquid. There is need to do further research of washing process by adding desinfection process.Â